2021
DOI: 10.5765/jkacap.210015
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Screen Overuse and Behavioral and Emotional Problems in Elementary School Children

Abstract: Objectives This study identified the association between excessive exposure to screen media and behavioral and emotional problems in elementary school students. Methods A total of 331 parents of children aged 7–10 years were recruited from “The Kids Cohort for Understanding of Internet Addiction Risk Factors in Early Childhood (K-CURE)” study. Children’s demographics, household media ownership, screen time, and behavioral/emotional problems were assessed using a parenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
9
0
4
Order By: Relevance
“…Regarding possible associations between PSU and children and adolescents’ health, previous studies reported negative associations with psychological well-being [ 25 27 ], mood [ 28 ], prosocial behaviour [ 29 ], peer relations [ 29 ], and academic performance [ 30 ] as well as positive associations with behavioural and emotional problems [ 31 ]. For excessive smartphone use, i.e., long usage times without considering symptoms of behavioural addiction, associations with poorer sleep quality [ 32 ], bad mood [ 33 ], low psychological well-being [ 34 ] and behavioural and emotional problems [ 35 ] were observed. It is important to mention that most previous studies on PSU were performed in Asian countries (especially South Korea [ 36 ]) and in older adolescents or young adults [ 15 , 17 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding possible associations between PSU and children and adolescents’ health, previous studies reported negative associations with psychological well-being [ 25 27 ], mood [ 28 ], prosocial behaviour [ 29 ], peer relations [ 29 ], and academic performance [ 30 ] as well as positive associations with behavioural and emotional problems [ 31 ]. For excessive smartphone use, i.e., long usage times without considering symptoms of behavioural addiction, associations with poorer sleep quality [ 32 ], bad mood [ 33 ], low psychological well-being [ 34 ] and behavioural and emotional problems [ 35 ] were observed. It is important to mention that most previous studies on PSU were performed in Asian countries (especially South Korea [ 36 ]) and in older adolescents or young adults [ 15 , 17 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to earlier studies, screen time was closely related to children’s sleep and behavioral problem. 34 However, this study showed that children’s sleep problems did not worsen in 2021; this might be due to the reopening of schools that allow them to relearn their previous regular morning routines and assisted in the prevention of the children’s sleep problems due to overnight smartphone use. This contradictory finding could be interpreted in a similar context as the results of previous studies that suggested the trajectory of recovery and adaptation.…”
Section: Discussionmentioning
confidence: 85%
“…These results are consistent with the results of previous studies showing that the low-income class was vulnerable to media overuse, sleep problems, and problematic behavior. 15 25 34 36 Family income, not only parental wellbeing, but access to an abundant resource of structured education and activity, is an important factor in establishing and maintaining a family's effective coping strategy. 37 However, how income affects other variables during COVID-19 needs to be investigated in detail through additional research.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, media addiction-related external problems are also reflected in sensation-seeking and rule-breaking behavior (Choi et al, 2021). Both internal and external behavioral problems and screen time, in general, are associated with social and academic adaptation, which consequently both affect school adaptation (Ahn et al, 2017;Choi et al, 2021;Lee and Lee, 2021;Lee and Park, 2022). Consequently, poor school adaptation can negatively impact academic and social aspects, further exacerbating the problem and creating a loop.…”
Section: Effect Of Digital Interaction Towards Wellbeingmentioning
confidence: 99%
“…Internal behavioral problems include psychological health where significant connections were particularly found with children's depression and social atrophy (Ahn et al, 2017;, whereas external behavioral problems include aggression and attention problems or difficulty focusing during class (Ahn et al, 2017;. Additionally, media addiction-related external problems are also reflected in sensation-seeking and rule-breaking behavior (Choi et al, 2021). Both internal and external behavioral problems and screen time, in general, are associated with social and academic adaptation, which consequently both affect school adaptation (Ahn et al, 2017;Choi et al, 2021;Lee and Lee, 2021;Lee and Park, 2022).…”
Section: Effect Of Digital Interaction Towards Wellbeingmentioning
confidence: 99%